2008
DOI: 10.1016/j.pt.2008.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Does activation of the blood coagulation cascade have a role in malaria pathogenesis?

Abstract: Plasmodium falciparum infection is often associated with a procoagulant state. Recent identification of tissue factor (TF) in the brain endothelium of patients who died from cerebral malaria casts new light in our understanding of the coagulation disorder found in P. falciparum infection. It has also been revealed that parasitized red blood cells (pRBC) support assembly of multimolecular coagulation complexes. In this article, the role of TF expression by the endothelium and amplification of the coagulation ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 52 publications
(103 reference statements)
2
54
0
Order By: Relevance
“…Differences in the clothing habits of males and females in India and also the feeding habits of Anopheles vectors in the evening and outdoors would have contributed to this difference in sex incidence. Thrombocytopenia (platelet count \150,000/mm 3 ) was present in almost all (97.5%) patients (78/80; P. vivax 39/40 and P. falciparum 39/40) in this study in accordance with similar high incidence reported by earlier studies [4,6]. In order to find correlation between thrombocytopenia and the presence or absence of hemorrhage, the platelet counts were categorized into five subgroups representing different degrees of thrombocytopenia (Table 8).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Differences in the clothing habits of males and females in India and also the feeding habits of Anopheles vectors in the evening and outdoors would have contributed to this difference in sex incidence. Thrombocytopenia (platelet count \150,000/mm 3 ) was present in almost all (97.5%) patients (78/80; P. vivax 39/40 and P. falciparum 39/40) in this study in accordance with similar high incidence reported by earlier studies [4,6]. In order to find correlation between thrombocytopenia and the presence or absence of hemorrhage, the platelet counts were categorized into five subgroups representing different degrees of thrombocytopenia (Table 8).…”
Section: Discussionsupporting
confidence: 92%
“…Role of circulating immune complexes and inflammatory mediators (e.g. TNF-a, IL-6 and Interferon) has also been postulated [4,6]. It is now well established that patients with thrombocytopenia due to peripheral destruction of normally functioning platelets and normal bone marrow (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…66 Malaria is also associated with activation of the coagulation and fibrinolytic pathways, with tissue factor activation suggested as the unifying mechanism in the pathology of severe malaria. 67 Disseminated intravascular coagulation can occur but is seen in only 1% of cases. 68 …”
Section: Hematologicalmentioning
confidence: 99%
“…However, most investigators propose that P. falciparum infection is associated with a procoagulant state (Francischetti 2008). Francischetti et al proved that the coagulation cascade played a crucial role in the pathogenetic processes leading to the cerebral complications (Francischetti 2008).…”
Section: Coagulation and CMmentioning
confidence: 99%
“…However, most investigators propose that P. falciparum infection is associated with a procoagulant state (Francischetti 2008). Francischetti et al proved that the coagulation cascade played a crucial role in the pathogenetic processes leading to the cerebral complications (Francischetti 2008). Tissue factor expression in the endothelium, and the amplification of the coagulation cascade by pRBCs and platelets at sequestration sites, contribute critically in initiating and maintaining a coagulation-inflammation cycle which leads to cerebral involvement in falciparum malaria (Francischetti 2008).…”
Section: Coagulation and CMmentioning
confidence: 99%